Tobacco use cessation interventions: Views and practices among clinical dental students in Chennai, India - Chandra Sekhara Reddy Vuyyuru; Jamil David; Rajeshree Narayan Rangari (Wolters Kluwer Medknow Publications, 2016)
Introduction: A dental visit provides the patient with an opportunity to discuss the habit of tobacco consumption and its detrimental effects on oral and general health. Cessation advice, as well as pharmacological therapy, has been used by health professionals to help patients quit tobacco use. Aim: To investigate the knowledge and practices of tobacco use cessation (TUC) interventions among final year students and interns in Chennai, India. Materials and Methods: A cross-sectional random sampling technique was used to collect information from final year students and interns, from four dental colleges in Chennai. Data regarding TUC interventions were obtained using a structured and self-administered questionnaire, comprising 30 questions. Results: A total of 53% and 47%, final year students and interns, respectively participated in the study. The response rate was 75%. Statistically significant associations were observed between the students' year of study and their views on the inclusion of TUC in clinical practice (P < 0.05) as well as the advice/interventions practiced by them (P < 0.05). Significantly higher proportions of interns, when compared to the final year students (P < 0.05) regarded periodontal disease as a symptom of tobacco consumption, agreed that tobacco use could cause implant failure, informed patients about the negative effects of smoking on oral health, discussed the ill-effects of passive smoking and admitted to helping their patients quit smoking. Conclusion: Several parameters related to TUC interventions were different among final year dental students and interns. This study reveals that significant numbers of dental students are not practicing any TUC methods in their routine dental curriculum which might help patients discontinue tobacco use.